2001
DOI: 10.1002/1521-4141(200107)31:7<2126::aid-immu2126>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Association of SLP-65 / BLNK with the B cell antigen receptor through a non-ITAM tyrosine of Ig-α

Abstract: The cytoplasmic adaptor protein SLP‐65 (BLNK or BASH) is a cricital downstream effector of the B cell antigen receptor (BCR). Tyrosine‐phosphorylated SLP‐65 assembles intracellular signaling complexes such as the Ca2 + initiation complex encompassing phospholipase C‐γ2 and Bruton′s tyrosine kinase. It is, however, unclear how the SLP‐65 signaling module can be recruited to the plasma membrane. Here we show that following B cell stimulation, SLP‐65 associates directly with the BCR signaling subunit, the Ig‐α / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 56 publications
(68 reference statements)
5
96
0
Order By: Relevance
“…In vivo, the main determinant of BLNK binding, Y 204 , is phosphorylated following receptor ligation. Furthermore, the SH2 domain of BLNK can bind directly to this phosphotyrosine (37,68). These data indicate that BLNK is recruited directly to Ig␣, the same chain to which Syk is recruited and activated, providing a mechanism to ensure rapid phosphorylation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In vivo, the main determinant of BLNK binding, Y 204 , is phosphorylated following receptor ligation. Furthermore, the SH2 domain of BLNK can bind directly to this phosphotyrosine (37,68). These data indicate that BLNK is recruited directly to Ig␣, the same chain to which Syk is recruited and activated, providing a mechanism to ensure rapid phosphorylation.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, Ig␣ contains two non-ITAM tyrosines at residues Y 176 and Y 204 . One study indicated that BLNK might bind to phosphorylated Y 204 ; however, the contribution of this association to signaling or receptor trafficking was not investigated (37).…”
mentioning
confidence: 99%
“…This hypothesis is corroborated by the observation that all signaling pathways emanating from CD25-SCIMP were abolished by mutation of the SLP65/SLP76 binding site. Notably, the BCR signaling subunit Ig␣ also contains a SLP65 binding tyrosine, and its mutation compromises the BCR signaling pathway (13,38). An opposite phenotype was observed when the Csk-binding tyrosine was mutated, since all the responses generated after cross-linking of CD25-SCIMP were substantially enhanced, indicating a direct role of Csk in the regulation of signaling mediated by SCIMP.…”
Section: Discussionmentioning
confidence: 99%
“…Following cell activation, these adaptors are brought to the plasma membrane. Their recruitment is largely dependent upon tyrosine phosphorylation of transmembrane proteins and can be accomplished either indirectly, as in the case of the inducible association between LAT and SLP76 mediated via a cytosolic adaptor, Gads, or directly, as in the complex of SLP65 and the BCR subunit Ig␣ (13). Once localized at the membrane, the SLP65/SLP76 proteins become phosphorylated by Syk family kinases and form complexes with various effector molecules, such as Nck and Vav, Tec family kinases, and PLC-␥1 or PLC-␥2.…”
mentioning
confidence: 99%
“…The earliest detectable biochemical event that follows BCR aggregation is increased activity of protein tyrosine kinases of the Src family (Lyn), resulting in phosphorylation of the tyrosine residues within the ITAMs of Ig␣ and Ig␤ and the non-ITAM tyrosine 204 of Ig␣ (8), subsequently followed by the initiation of several signaling pathways (reviewed in Refs. 6, 9, and 10).…”
Section: Hs1-associated Protein X-1 Interacts With Membrane-boundmentioning
confidence: 99%